Influence of Parenting Styles on Suicidal Tendencies in High School Students - Cao, Chengyuan; Hao, Yutian (Transactions on Social Science, Education and Humanities Research, 2024)
The problem of high school student suicide is the focus of the current social concern, some researchers have found that parenting style has a significant effect on high school students’ suicidal tendencies, but there is a lack of unified explanation for the formation mechanism behind it. Therefore, this paper takes the influence of parenting styles on high school students’ suicidal tendencies as the research theme and utilizes the questionnaire survey method to explore the connection between the two. The study shows that authoritarian parenting style and permissive parenting style have a significant effect on high school students’ suicidal tendencies, and high school students under these two parenting styles have significant suicidal tendencies, while authoritative parenting style has no significant effect, and their children do not show significant suicidal tendencies. This study shows that the suicidal tendency of high school students is closely related to family parenting styles. Therefore, it is recommended that parents should choose appropriate ways to raise their children and pay attention to their children’s mental health.